Pengaruh Animasi Upin dan Ipin terhadap Kemampuan Bercerita Anak Usia Dini - Pasaribu, Felisia Junisi; Ismet, Syahrul (Lembaga Yasin AlSys, 2024)
This study aims to analyze the impact of Upin and Ipin animation on the storytelling ability of early childhood children who attend Yari International School Kindergarten in Padang City. The research conducted was a quantitative experiment. The study population consisted of students enrolled at Yari International School Kindergarten. Research sample was collected using purposive sampling. Data analysis compares two groups using uji-t. Research demonstrates that eksperimen classrooms gain 16.30 and control classrooms 13.70. Significant discrepancies exist between the two groups' employment of H₁ and Hₒ hypotheses. Thus, animasi upin and ipin affect kid storytelling early age.